The Place Based Policies: The Way Forward to Alleviate Poverty from Cities A Study of Bengaluru India - Mahamad, Jamadar Mudassar (H. : ĐHKT, 2020)
There is no second thought that the poverty is biggest enemy of humanity and every thought, effort and support made to defeat this enemy has to be appreciated. The concept of Poverty, though tricky to define, has well understood through the long and rich debate around it. The eager among the governments to know the numbers of poor in a country and region has convinced scholars to work on issues related to measurement and estimation of poverty. According to Sen (1981) scholars are largely using economic approach, anthropological interpretations and somewhat capability approach to explain the characteristics of poverty. The economic approach is easy to understand through income poverty line where if HH‟s income falls below a particular threshold amount that household considered as a poor, and then with calorie consumption norms where specific amount of calories decided necessary for an individual separately in rural and urban areas and whose consumption/ intake falls below the given norm is considered poor other than that anthropological interpretations are based on people‟s own conception of disadvantage, and capability approach is defined by its choice of focus upon the moral significance of individuals‟ capability of achieving the kind of lives they have reason to value. Later asset vulnerability framework has been given by Caroline Moser in 1998. This is the first time in history where poor are assessed based on what they have rather than what they do not have, simply in this approach the focus of the assessment is based on people‟s assets (Moser, 1998).